Two-Stage Semi-Continuous 2-Keto-Gluconic Acid (2KGA) Production by Pseudomonas plecoglossicida JUIM01 From Rice Starch Hydrolyzate - Sun, Lei; Wang, Da-Ming; Sun, Wen-Jing; Cui, Feng-Jie; Gong, Jin-Song; Zhang, Xiao-Mei; Shi, Jin-Song; Xu, Zheng-Hong (Frontiers in Bioengineering and Biotechnology, 2020)
A two-stage semi-continuous strategy for producing 2-keto-gluconic acid (2KGA) by Pseudomonas plecoglossicida JUIM01 from rice starch hydrolysate has been developed. Initial glucose concentration (140 g/L) was selected for first-stage fermentation due to its highest 2KGA productivity of 7.58 g/(L•h), cell weight of 3.91 g/L, and residual glucose concentration of 25.00 g/L. Followed by removing 70.0% (v/v) of first-stage broth and feeding 400.0 g/L of glucose to second-stage fermentor, a total of 50680.0 g glucose was consumed, and 50005.20 g 2KGA was obtained with a yield of 0.9867 g/g by P. plecoglossicida JUIM01 after 3-cycle two-stage semi-continuous fermentation. Our results indicated that the developed two-stage semi-continuous fermentation could be industrially applied due to its high 2KGA concentration, 2KGA yield and operation efficiency.